Vostok Bay: interseasonal changes in hydrological, hydrochemical and microbiological properties - N. K. Khristoforova; A. Yu. Lazaryuk; E. V. Zhuravel; T. V. Boychenko; A. A. Emelyanov (Известия ТИНРО)
Current ecological state of the Vostok Bay (Peter the Great Bay, Japan Sea) in spring, summer, and autumn seasons is described on the data of CTD profiling, chemical analysis of the water sampled at the sea surface and bottom, and microbial indication of the surface water. Strong seasonal variations are revealed for all examined parameters, driven by monsoon cycle. The winter monsoon in autumn with northwestern wind predominance causes the river runoff weakening and off-shore surge with the water removal from the top of the bay and the compensating inflow along the eastern coast distinguished by heightened values of salinity and dissolved oxygen and low values of biochemical oxygen demand (BOD5 < 1 mg/L). The summer monsoon in spring and summer with southeastern winds increases the river runoff and simultaneously the inflow of fresh water from the open sea, so causes a sharp difference in the water properties between parts of the Vostok Bay. Bioproductivity increases in these seasons that is reflected in increasing of BOD5 (up to 2 mg/L and sometimes more) and organic phosphorus concentration (up to 50 μg/L and more). In July, when the river runoff is blocked in the northwestern sector of the bay by onshore surge, the maximum number of bacteria is recorded there (up to 105 CFU/mL), including Escherichia coli group at all coastal stations in concentrations of 10–100 CFU/mL, which are not observed in the central and open parts of the bay. Among the groups of metal-resistant microorganisms, relative abundance of nickel-resistant bacteria is noted (up to 103 CFU/mL) that is a sign of hydrocarbon fuels combustion. The hydrocarbon pollution is confirmed by ubiquitous distribution of oil-oxidizing and diesel-resistant microorganisms detected mostly (up to 2.8 ∙ 104 CFU/mL in summer) in the northern part of the bay. Generally, the internal northern part of the bay is distinguished by high abundance of microorganisms belonged to different ecological and trophic groups, because of mutual impacts of the rivers, the coastal highway, nearby settlements, and sandy beaches occupied by vacationers in summer.